Toll like receptor 4 signaling pathway participated in Salmonella lipopolysaccharide-induced spleen injury in young chicks. (November 2017) - Li, Ningya; Ansari, Abdur Rahman; Sun, Zhijian; Huang, Haibo; Cui, Lei; Hu, Yafang; Zhao, Xing; Zhong, Juming; Abdel-Kafy, El-Sayed Mahfouz; Liu, Huazhen
Abstract: Spleen is one of the crucial sites for cellular and humoral immunity but it easily damaged during pathogenic infections resulting in immunosuppression. The current study was therefore performed to explore the mechanism of acute spleen injury induced by salmonella lipopolysaccharide (LPS) in young chicks. Healthy one-day-old Cobb strain broiler chicks were intra-peritoneally injected with saline or LPS. LPS treatment caused significant decreases in body and spleen weights at 36 and 72 h. Histological analysis showed the changes of ellipsoid structures with beginning of nuclear pyknosis and karyolysis similar to steatosis at 12 h, maximum histopathological lesions were seen at 36 h, however these were disappeared at 72 h post LPS stimulation. Cell proliferation was decreased (low PCNA positivity) and apoptosis increased (high ssDNA positivity) in the spleen at 12 and 36 h after LPS treatment. The expression levels of mRNA for caspase-3, caspase-8, B-cell lymphoma 2 (BCL-2), tumor protein p53 or p53 and Bcl-2 homologous antagonist killer (BAK) showed slight increase at some time points following LPS stimulation. LPS treatment also induced significant up-regulation in toll like receptor 4 (TLR4) at 36 h post LPS stimulation and slight increase in expressions of its downstream molecules (MyD88 and NF-κB) at 12 h post LPS treatment. The keystone cytokines (TNF-α and IL-6) exhibited significant up-regulation at 12 h following LPS stimulation. Our findings provided novel information about the histopathological as well as apoptotic and proliferative alterations in spleen mediated by TLR4 signaling induced by Salmonella LPS in avian species. Highlights: Spleen is an important immune organ but it may be damaged during pathogenic infections. Lipopolysaccharride (LPS) is a key component of cell wall in Gram-negative bacteria. LPS causes release of several mediators and cytokines leading to tissue injury in many vertebrates. The effect of intra-peritoneal Salmonella LPS injection in chick spleen is not fully explored yet. Herein, Salmonella LPS-induced alterations in chick spleen are mediated by toll like receptor 4 signaling pathway.